Biosorption of Cadmium(II) from Aqueous Solution by Fruiting Body of Agaricus blazei Murill - Yang, Mei-Zhizi; Liu, Gao-Xiang; Sun, Li-Ping (Asian Journal of Chemistry, 2015)
Fungal organisms can remove heavy metals from aqueous solutions. The aim of this study was to investigate the removal of cadmium by the fruiting body of Agaricus blazei Murill (AbM). Batch experiments were carried out to investigate the effect of pH, biosorbent dose, contact time and initial cadmium concentration on biosorption efficiency. The desired pH, biosorbent dose and contact time for the removal of cadmium was found to be 6, 2 g/L and 180 min, respectively. The percent removal of cadmium was found to increase with the increase in biosorbent dosage and contact time and the adsorption capacity was found to increase with the increase in initial cadmium concentration. The fitness of the biosorption data for Langmuir, Freundlich and Dubinin-Radushkevich (D-R) adsorption models was investigated. It was found that biosorption of cadmium onto the biomass of Agaricus blazei Murill was better suitable to Langmuir than Freundlich and D-R adsorption model. For four kinetics models, the kinetics of cadmium adsorption was very well described by the pseudo-second-order kinetic model (R2 > 0.99) and the liquid film diffusion process is the rate-limiting step occurring during biosorption of cadmium. The thermodynamic parameters showed the exothermic and spontaneous nature of the biosorption of cadmium onto Agaricus blazei Murill.